Women suffering from endometrioma-related symptoms may benefit from Silymarin, an antioxidant - Mufti, Amna Faheem; Rizwan, Abdul Wahid; Farooq, Hassan (Journal of the Pakistan Medical Association, 2023)
Madam, Endometriosis is a potentially debilitating disease in which endometrial tissue is present outside the uterine cavity. It can be symptomless in some women, while causing severe pelvic pain, dysmenorrhea, dyspareunia, and decreased fertility in others.1 According to the World Health Organisation (WHO), endometriosis affects 10% (190 million) of reproductive age women globally.2 Endometriomas are the most common manifestation of endometriosis on the ovary, indicating a more severe disease state.3 In October 2022, a randomised trial was conducted to study Silymarin’s efficacy on endometrioma-related manifestations. 4 The trial was the first of its kind. It showed that Silymarin, a herbal supplement with potent antioxidant effects, significantly decrease endometrioma size and the chronic pelvic pain related to it.4 Oxidative Stress, an imbalance between ROS and antioxidants, is known as a primary factor in the endometriosis pathogenesis5, and Silymarin may be ten times as potent as Vitamin E, another antioxidant which has been investigated in relation to endometriosis treatment.4 In Pakistan, the estimated prevalence of endometriosis is 16.8%6, which means a significant number of women are living with the manifestations that come with the disease, including endometriomas, which are seen in 17 to 44% of individuals with endometriosis.3 Silymarin is already available and used in Pakistan for its hepatoprotective effects. In light of this, it is of great importance that this new treatment and its effects are studied on a larger scale, specifically on the Pakistani population to learn more about its potential in reducing the suffering and improving the quality of life of these women.